INDEKS KEPUASAN MASYARAKAT (IKM) DALAM PELAYANAN SIM PADA SATLANTAS POLRES DUMAI - Hildawati (Jurnal Niara, 2019)
Service quality is one of the important studies in bureaucratic reform. Until now, the problems of services provided by the government/ state to the people who make arrangements tend to still have many complaints. Such as the issue of service time which is not in accordance with the standards, convoluted service procedures to the problems of facilities and infrastructure which are considered to be less supportive of the implementation of services. At the Satllantas Polres Dumai, the same problems still occur, including in the service of obtaining a driver's license (SIM). Through Minister of Administrative Reform and Bureaucratic Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys in this study a survey was conducted to find out people's perceptions and satisfaction with the services performed by the Satlantas Polres Dumai in servicing people who manage SIMs. The survey method refers to the provisions in the Minister of Administrative Reform and Bureaucratic Reform Regulation No. 14 of 2017 concerning Guidelines for Preparing the Community Satisfaction Survey. From the results of the study it is known that the IKM value of service quality in obtaining a SIM at the Satlantas Polres Dumai is 3.16 which is in the interval 2.51 - 3.25. Based on these results, the conversion value of IKM obtained is 78.94, which is in the intervals of 62.51 - 81.25 with service quality is B and service performance is categorized as GOOD